The effects of testosterone on embodiment: implications for social power - Minné, Donné (Department of Psychology, 2019)
Following recent trends in the neurosciences in which the body is seen as a constituting factor in mental experience and behavior, this thesis examined the role of testosterone in mapping the state of the body. The general aim was thus to contribute to the literature on the embodied basis of power by asking whether a change in the neurochemistry associated with social power has any effect on embodiment? Accordingly, in a series of randomized, double-blind, placebocontrolled studies, this thesis assessed for the first time the effects of a 0.5mg dosage of testosterone on three important dimensions of embodiment in samples of women: 1) The perception of internal physiological signals (interoception), 2) Body ownership, and 3) The experience of sensory-motor agency. Psychological tests measuring emotion and personality were integrated into the design. Using a heartbeat tracking task, testosterone was shown to increase interoceptive accuracy at baseline, but this advantage was lost following ostracism in an online ball tossing game. In experiment two, it was found that testosterone compared to placebo prevented a decline in limb temperature during the Rubber Hand Illusion, a commonly used paradigm for manipulating experiences of body ownership and for measuring homeostatic changes related to disembodiment. In experiment three, testosterone was found to increase the implicit sense of agency as measured in terms of intentional binding, a task which exploits the tendency to perceive a contraction in time when one’s own actions are felt to be casually related to external effects. Results indicate that testosterone has the capacity to improve interoceptive accuracy, is able to help regulate homeostasis in response to erroneous top-down beliefs about the body, and to increase the feeling of sensorimotor control. While the limitations of this data are acknowledged, these main findings suggest that testosterone is able to modulate the experience and representation of the body and offer insight into some of the rudimentary embodied mechanisms via which the hormone might support the rise to power.